Liver stiffness measurements and FIB-4 are predictors of response to sofosbuvir-based treatment regimens in 7256 chronic HCV patients. (3rd October 2019) - Abdel Alem, Shereen; Elsharkawy, Aisha; El Akel, Wafaa; Abdelaziz, Ashraf O; Salama, Rabab Maamoun; El-Sayed, Manal Hamdy; El Kassas, Mohamed; Anees, Mahmoud; Shedeed, Mahmoud; Abdelsalam, Fatma; Ziada, Dina H; El Shazly, Yehia; et al.
ABSTRACT: Objectives : To assess the role of baseline liver stiffness (LS) by Transient elastography (TE) and FIB-4 in the prediction of virological response to sofosbuvir – based regimens in chronic HCV patients. Methods : A retrospective, multicenter study including 7256 chronic HCV patients who received different sofosbuvir–based regimens. Baseline demographic and laboratory data were recorded. TE was performed with FIB-4 calculation at baseline. Results : Sustained virological response at week 12 post-treatment (SVR12) was 91.4%. Pretreatment TE values and FIB-4 were significantly lower among sustained responders (17.8 ± 11.5 kPa, 2.66 ± 1.98, respectively) versus relapsers (24.5 ± 13.9 kPa, 4.02 ± 3.3, respectively). Best cutoff levels for LS by TE and FIB-4 score for prediction of failure to treatment response were 16.7 kPa and 2.4, respectively. Among different treatment protocol, patients with FIB-4 > 2.4, TE values >16.7 kPa are more prone to treatment failure except when using SOF/SIM treatment regimens. Conclusion : Baseline LS by TE and FIB-4 score may be useful for predicting treatment outcome in the new era of DAAs and could be integrated into pretreatment assessment of chronic HCV patients for better optimization of patient management.